A mitochondria-targetable fluorescent probe for peroxynitrite: fast response and high selectivity1. Issue 13 (14th February 2015) - Zhang, Hongxing; Liu, Jing; Sun, Yuan-Qiang; Huo, Yingying; Li, Yaohua; Liu, Weizhi; Wu, Xiao; Zhu, Nishu; Shi, Yawei; Guo, Wei
<x xml:space="preserve">Abstract</x> A mitochondria-targetable fluorescence probe, methyl(4-hydroxyphenyl)amino-substituted pyronin (1), was exploited, which could highly selectively sense peroxynitrite (ONOO−) within seconds.